Important aspects of integrated learning in foreign language classes in higher education institutions - Суханова, Тетяна Євгенівна; Коляда, Ірина Валеріївна (Університет Григорія Сковороди в Переяславі, 2025)
Дана стаття присвячена інтегрованому навчанню, яке є ефективним підходом до викладання іноземних мов у вищих навчальних закладах. Автори переконані, що інтегроване навчання сприяє формуванню міждисциплінарного мислення, критичного аналізу та здатності до міжкультурної комунікації. У дослідженні розглядаються інтегративні методи, які забезпечують розширення професійного словникового запасу студентів, розвиток їхніх комунікативних навичок, формування умінь працювати в команді та самостійно, інтеграцію мовленнєвого та предметного навчання, що готує конкурентоспроможних фахівців

This article is dedicated to integrated learning as an effective approach to teaching foreign languages in higher education institutions. The authors argue that integrated learning promotes the development of interdisciplinary thinking, critical analysis, and intercultural communication skills. The study examines integrative methods that ensure the expansion of students’ professional vocabulary, the development of their communicative skills, the formation of teamwork and independent working abilities, as well as the integration of language and subject learning, which prepares competitive specialists
Keywords: вища освіта; викладання іноземних мов; інтегроване навчання; комунікативні навички; критичне мислення; лінгвістична компетентність; higher education; foreign language teaching; integrated learning; communicative skills; communicative skills; linguistic competence